Response of mixed viable probiotics culture on milk production and nutrient availability in crossbred mid lactating cows - DUTTA, T K; KUNDU, S S (The Indian Journal of Animal Sciences, 2011)
Effect of feeding probiotics culture in triple combination (Saccharomyces cerevisiae, Lactobacillus plantarum and Enterococcus faecium; ratio 6: 2: 2, total dose lOxl09 cfu/animal) to crossbred mid lactating cows was studied to observe the lactation performance and nutrient utilization. Dry matter intake (DMI)/100 kg body weight tended to increase due to inclusion of probiotics culture and significant between control (T1) and treatment groups (T2) in second (PÂ